Asociace aterotrombózy a trombofilie - genetické aspekty - Kvasnička, Tomáš (Vnitrni lekarstvi, 2014)
Thrombosis in the arterial or venous vascular systems is preceded by a complex interplay between environmental and genetic factors, and it is the underlying cause of several common complex diseases. The genomewide association approach has proved successful in identifying loci associated with cardiovascular disease and related risk factors. However, much work remains to identifyning the culprit genes and causal variants as well as the mechanisms whereby they influence disease development and progression. In-depth studies of previously identified disease-associated loci are expected to improve our understanding of the pathophysiology of cardiovascular disease and identify novel targets for treatment. In the field of atherothrombosis and thrombophilia are significant results from association studies focused on the area of coronary artery disease, ischemic stroke, venous thromboembolism.Key words: atherosclerosis - atherothrombosis - coronary artery disease - genomewide association study (GWAS) - myocardial infarction - single nucleotide polymorphism (SNP) - thrombophilia - venous thromboembolism.
Keywords: celogenomová asociační studie; Genome-Wide Association Study; Thrombophilia; rizikové faktory; Humans; ateroskleróza; trombofilie; lidé; Atherosclerosis; Genetic Predisposition to Disease; genetická predispozice k nemoci; Risk Factors